Minarets and golden arches: state, capital and resistance in neoliberal Turkey - Altinors, Gorkem (2016)
The main purpose of this thesis is to critically analyse the convergence of political Islam and neoliberalism in Turkey. By doing so, the research aims to construct a Gramscian historical materialist account as opposed to the mainstream centre-periphery relations approach. The mainstream centre-periphery relations approach takes the state and civil society as antagonistic autonomous entities. This consideration brings us where the Turkish politics are perceived as a terrain of conflict between Islamists and secularists. The centre-periphery relations approach has four shortcomings. First, the state and society are considered separately. Second, the market and the state; and the economy and the politics are considered separately. Third, as considered separately, the theory takes civil society as automatically progressive. Fourth, the social relations of productions are neglected. This thesis argues that the Islamists versus secularists dichotomy is not sufficient enough to explain the complexity of contradictions in Turkish politics because of the given four shortcomings. Therefore, a more complex theory where the antagonism is considered within the class struggle is needed. Antonio Gramsci’s theory of hegemony, passive revolution and most importantly the integral state provides a new window in this respect. The Gramscian historical materialism offers a holistic understanding for the relationship between the state and society, the market and the state, and the economy and the political. As part of the hegemonic struggle, civil society can be on either side of the struggle therefore it is not considered as automatically progressive in Gramscian historical materialism. As a historical materialist approach, Gramscianism considers the social relations of production as the crucial element of the analysis. The pre-2002 periods (before the Justice and Development Party came into power) were already researched by Gramscian scholars. Therefore, the neoliberal restructuring in Turkey during the Justice and Development Party era is the focal period of this thesis. There will be a specific focus on the cases of urbanisation, education, and the mass media. The conceptual framework of state-society relations is the analytical basis of this study. Overall, this thesis offers an alternative reading of the rise of political Islam in Turkey.